The syntax of adjuncts - Ernst, Thomas Boyden (Cambridge University, 2013)
This book proposes a theory of the distribution of adverbial adjuncts in a Principles and Parameters framework, claiming that there are a few syntactic principles specific to adverbials; rather, for the most part, adverbials adjoin freely to any projection. Adjuncts' possible hierarchical positions are determined by whether they can receive a proper interpretation, according to their selectional (including scope) requirements and general compositional rules, while linear order is determined by hierarchical position along with a system of directionality principles and morphological weight, both of which apply generally to adjuncts and all other syntactic elements. A wide range of adverbial types is analyzed; predicational adverbs (such as manner, and modal adverbs), domain expressions like financially, temporal, frequency, duration, and focusing adverbials; participant PP's (e.g. locatives and benefactives); resultative and conditional clauses, and others, taken primarily from English, Chinese, French, and Italian, with occasional reference to others (such as German and Japanese).